Tinjauan COVID-19 pada Anak: Infeksi hingga Terapi - Rismala Dewi (Majalah Kedokteran Indonesia, 2020)
Coronavirus disease 2019 (COVID-19) is an acute respiratory infection which is caused by SARS-CoV-2 virus. Studies showed that the transmission of the virus is from human to human the primary transmission of SARS-CoV-2 infection is via droplets produced by sneezing or coughing. There is a possibility that COVID-19 can be transmitted through aerosol or airborne transmission. The incubation period of this infection is predicted to be between 3-14 days after close contact. Patients with COVID-19 could have various clinical manifestations from asymptomatic to respiratory failure. Although a few cases revealed that COVID-19 could result in critical condition, COVID-19 is relatively mild in children. Physicians must diagnose and assess the clinical severity of the patient with SARS-CoV-2 infection as it affects the management of the disease. Several anti-viral medicines that might be effective in treating COVID-19 patients such as Remdesivir, Chloroquine/Hydroxychloroquine, Lopinavir-Ritonavir, and Tocilizumab are currently still on trial. It is also crucial to prevent the spread of COVID-19 by encouraging people to apply hand-hygiene, practice social distancing, and disinfect all possible sources.